2019
DOI: 10.1002/ehf2.12416
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow and plasma FGF‐23 in heart failure patients: novel insights into the heart–bone axis

Abstract: Aims Fibroblast growth factor 23 (FGF‐23) is known to be elevated in patients with congestive heart failure (CHF). As FGF‐23 is expressed in the bone but can also be expressed in the myocardium, the origin of serum FGF‐23 in CHF remains unclear. It is also unclear if FGF‐23 expressed in the bone is associated with outcome in CHF. The aim of the present study was to investigate FGF‐23 levels measured in bone marrow plasma (FGF‐23‐BM) and in peripheral blood (FGF‐23‐P) in CHF patients to gain furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
3
15
0
2
Order By: Relevance
“…The fact that the association between estimated NHANES FGF-23 values and CV and all-cause mortality was similar to what was observed by Haring and colleagues provides some support for the external validity of their equation. It is also interesting to note that the estimated FGF-23 levels for NHANES patients with CHF (not included in the Haring equation) were more than twice as high as among those without CHF, consistent with findings from other studies [36]. Nevertheless, the strength of our results hinge upon the strength of the assumption that the Haring equation can be validly extended to the broader NHANES population, an assumption that could best be tested were directly measured FGF-23 to be included as part of a future wave of NHANES.…”
Section: Discussionsupporting
confidence: 88%
“…The fact that the association between estimated NHANES FGF-23 values and CV and all-cause mortality was similar to what was observed by Haring and colleagues provides some support for the external validity of their equation. It is also interesting to note that the estimated FGF-23 levels for NHANES patients with CHF (not included in the Haring equation) were more than twice as high as among those without CHF, consistent with findings from other studies [36]. Nevertheless, the strength of our results hinge upon the strength of the assumption that the Haring equation can be validly extended to the broader NHANES population, an assumption that could best be tested were directly measured FGF-23 to be included as part of a future wave of NHANES.…”
Section: Discussionsupporting
confidence: 88%
“…Fibroblast growth factor 23 (FGF‐23), a bone‐derived hormone regulating renal phosphate homeostasis and vitamin D metabolism, has a direct action on the cardiovascular system and has been recently related to adverse cardiovascular events in chronic HF and implicated in cardiac remodelling 6–9 . Several recent studies suggested that higher FGF‐23 levels were associated with left ventricular hypertrophy 10 and worse prognosis, particularly among patients with chronic kidney disease (CKD) 11,12 but also in stable ischaemic cardiomyopathy 13 and HF with reduced ejection fraction (HFrEF) 6–8,14–16 . FGF‐23 has also been identified as a biomarker significantly related to atrial fibrillation 17 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the meta-analysis by Marthi et al (2018) did not find a trend across different levels of kidney function in the association between high FGF-23 and HF. From a cardiac functional point of view, many studies have correlated high plasma levels of FGF-23 with a reduced left ventricular ejected fraction (LVEF; <40%), which indicates that high FGF-23 levels are directly linked to systolic dysfunction (Seiler et al, 2011;Shibata et al, 2013;Agarwal et al, 2014;Poelzl et al, 2014;von Jeinsen et al, 2019;Song et al, 2021). Furthermore, high plasma levels of FGF-23 are also associated with albuminuria in CKD which is strongly associated with Heart Failure with reduced Ejection Fraction (HFrEF), but not with Heart Failure with preserved Ejection Fraction (HFpEF) (Nayor et al, 2017).…”
Section: Fgf-23 and Hfmentioning
confidence: 99%
“…FGF-23 is an early and complementary predictor of adverse cardiac events and could be suitable for improving risk assessment in vulnerable patients with HF or reduced ejection fraction ( Koller et al, 2015 ). FGF-23 is positively correlated with but does not directly depend on the classical biomarkers of cardiac damage, such as N-terminal-pro-B-type natriuretic peptide (NT-proBNP) ( Seiler et al, 2011 ; Shibata et al, 2013 ; Kestenbaum et al, 2014 ; Poelzl et al, 2014 ; Koller et al, 2015 ; Masson et al, 2015 ; Panwar et al, 2015 ; Speer et al, 2015 ; Wohlfahrt et al, 2015 ; Ter Maaten et al, 2018 ; von Jeinsen et al, 2019 ; Song et al, 2021 ), high-sensitive cardiac troponin T (hs-cTnT) ( Kestenbaum et al, 2014 ; Masson et al, 2015 ; Song et al, 2021 ) and C-reactive protein (CRP) ( Parker et al, 2010 ; Seiler et al, 2011 ; Ix et al, 2012 ; Lutsey et al, 2014 ; Panwar et al, 2015 ; Speer et al, 2015 ; Reindl et al, 2017 ; Song et al, 2021 ). Furthermore, it has already been demonstrated that the predictive value of the combination of these biomarkers on cardiovascular risk assessment is significantly greater than any of them alone ( Wohlfahrt et al, 2015 ).…”
Section: Clinical Variables and Cardiac Events Associated With High Cmentioning
confidence: 99%
See 1 more Smart Citation